Analyzing the macro-level determinants of user entrepreneurship. The moderating role of the national culture. Issue 3 (15th March 2021) - Kalisz, David; Schiavone, Francesco; Rivieccio, Giorgia; Viala, Céline; Chen, Junsong
ABSTRACT: Scholars have extensively analysed country-based determinants of entrepreneurship over the last few decades. One of these is national culture. To date such a body of knowledge was underestimated in one of the rising streams of literature observed over the last decade: user entrepreneurship. To fill this research gap, the research questions of the present paper are: What is the impact of country-level factors on user entrepreneurship? What is the role of culture in such a relationship? The study analyzes new business units' activities created by user innovators in the healthcare industry, exploring the effects of the four dimensions of the entrepreneurship model by Thai and Turkina. The adopted methodology uses statistical methods based on principal component analysis (PCA), cluster analysis, and polynomial regression models. Findings indicate a clustering behaviour among countries with similar user entrepreneurial activities. Such behaviour highlights the macro-level determinants of health user entrepreneurship, defining a curvilinear relationship among these. In particular, an inverted U-shaped curve emerges when user entrepreneurship is combined with a country's health culture. We detect a moderation effect of national culture on such a nonlinear relationship at the cross-country level.